Efficacy and Side Effects of Topical Applications of Two Different Solutions in the Treatment of Molluscum Contagiosum in a City in Africa: An Open, Randomized, Comparative Clinical Trial - Kibar Ozturk, Melike (Journal of Pediatric Infectious Diseases, 2019)
Molluscum contagiosum (MC) is one of the most common viral infections in African children. However, there is no work investigating the treatment of MC in dark skinned children in Africa. In this study, we aimed to compare efficacy and side effects of topical application of 10% potassium hydroxide (KOH) and 16.7% salicylic acid (SAL) and lactic acid (LAC) combination in the treatment of MC in Sudan, Africa. This is a prospective, randomized, and comparative study. The inclusion criterion was the presence of at least 10 lesions. The exclusion criteria were the use of any topical MC treatment during the last 2 weeks, immunosuppression, periorbital and perioral involvement, the history of hypersensitivity to any kind of keratolytics, and the presence of concomitant bacterial skin infections. The main efficacy outcome was the complete remission or partial remission. Three visits were performed: baseline visit (diagnosis, randomization, and therapy initiation), visit 1 for follow-up (at 15–30 days after initiation of therapy and for study end), and visit 2 for postclearing assessment (at 60th day after the initiation of therapy). Chi-squared (χ2) test was used. All patients (n = 101) participating completed the 60 days of follow-up period. Post 60 days of treatment, the rates of complete resolution in 55 patients treated with 10% KOH solution and 47 patients treated with 16.7% SAL + LAC combination solution were 87.0 and 85.1% (p > 0.05), respectively. The rates of partial resolution in the group treated with KOH solution and in patients treated with SAL + LAC combination solution were 12.9% and 14.8% (p > 0.05), respectively. Major side effects in KOH group were burning sensation or stinging during application (48.1%, p = 0.0009) and hypopigmentation (38.8%, p = 0.007) while it was desquamation (23.4%, p > 0.05) in the SAL + LAC combination group. Results indicate both 10% KOH solution and SAL + LAC combination solution showed good efficacy in the treatment of MC in African children. Neither 10% KOH nor the SAL + LAC combination solution was found superior to other in the treatment, while the latter was noted to have fewer side effects. Permanent hypopigmentation is an important and undesired side effect of 10% KOH treatment.
Keywords: molluscum contagiosum; potassium hydroxide; salicylic acid; lactic acid